Polymer based optical MEMS (POEMS) - Franck Chollet. (2009)
MEMS application to photonics and optics have been of interest to researchers for a long time, and have recently emerged in some very successful products. The DLP from Texas Instrument, which is used in many consumer video projects and power-up the digital cinema all around the world, is probably the best example of such achievement. But the miniaturization of optical component has more market potential than video projector alone and the microlens arrays used to increase the efficiency of CMOS camera in handphone or the optical switches used for optical fiber telecommunication are testimony of a growing field. In this project we have been exploring applications of optical MEMS based on microlenses and on integrated optics. We choose these two domains more particularly as they could be applied to a wide range of fields, from optical telecommunication to sensing or biomedical. Moreover we choose to depart from traditional work done in the field and pursue the development of hybrid structure based, as usually, on silicon for the mechanical or structural part but using polymer for the optical part. The main reason behind this choice is the perceived superiority of polymers over silicon as optical material, particularly in the visible domain where silicon is opaque. We first studies in theory and in practice the micro-fabrication of different micro-optical elements like mirrors or lenses, a work conducted mainly as the research project of a MEng student. We particularly focused on a special technique known as reflow that allows easy production of structure with 3D spherical profile. This technique is ideal for micro-lenses and we developed a theoretical framework for predicting the optical characteristics from the process parameters. After proposing different improvements to the technique, we used it in an imaging system for endoscopic application. In parallel, as the work of PhD student, we studied optical waveguide based devices, studying coupling and propagation problems and developing different techniques for fabrication with polymer. We applied this to the fabrication of an original optical switch with many interesting properties, for which we developed a latching actuator with a new process that we called “single step etch and release”. Other applications to sensing, tissue engineering and metrology were also pursued through different collaborations, where we contributed expertise in optics and polymer processing. As such we worked both with colleagues in our organization (A/P V. Murukeshan, A/P Nam-Trung Nguyen – NTU) and outside (A/P Etienne Burdet, A/P Dietmar Hutmacher – NUS, Dr Stuart Springham – NIE, Dr Ramana – IME) as well as in companies (Valen Technology, Hong Leong Eng.). These cooperative works resulted in several publications and in a US patent for an opto-fluidic sensor that is now being developed by a German company.